Whither Singapore banking? - Chew, Adrienne Kah Woon. (2008)
This study deals with the Singapore banking sector: its past, present and projected future. The rapid pace of change in the sector has caused much of the literature on it to be outdated. This study offers an updated insight on the industry, incorporating events that have occurred up to the end of 1998, and some notable events that have taken place since. These developments are expected to have a significant impact on the face of Singapore banking as we know it today.